Comparative Study of Frequency of Placenta Previa in Women with History of Cesarean Delivery Versus Normal Vaginal Delivery - Bakhtawar; Hamza , Summaira; Saleem , Zamrad; Khan , Maleeha; Ruqia , Bibi; Hira (Indus Journal of Bioscience Research, 2025)
Background: Placenta previa, where the placenta partially or completely covers the cervix, is a major obstetric concern. Risk factors include multiparity, advanced maternal age, prior cesarean deliveries, and uterine surgeries. This study compares its prevalence in women with previous cesarean versus natural births. Objective: To assess the prevalence of placenta previa in women with prior cesarean deliveries compared to those with previous vaginal births, considering associated risk factors like multiparity, advanced maternal age, and uterine surgeries. Methodology: At Quetta tertiary care hospital Quetta, a comparative cross-sectional study was carried out. One hundred pregnant women with placenta previa were enrolled in the study; they were split into two groups: fifty who had previously had cesarean births and fifty who had previously given birth vaginally. Clinical observations, structured interviews, and inspections of medical records were used to gather data. To determine the prevalence of placenta previa and the risk factors and consequences that are linked to it, statistical analysis was done. Results: The results showed that women with a history of cesarean delivery had a considerably higher prevalence of placenta previa (36%) than women with a history of vaginal delivery (12%). The likelihood of placenta previa rose with the number of prior cesarean procedures, indicating a dose-response link. The cesarean group experienced higher maternal problems, including antepartum and postpartum hemorrhage. Furthermore, placenta previa cases were associated with an increased risk of fetal problems, such as preterm birth and neonatal intensive care unit admission, especially in women who had previously had cesarean births. Conclusion: Previous cesarean deliveries significantly increase the risk of placenta previa. Careful consideration of cesarean sections, proper prenatal care, and risk assessment are crucial to improving maternal and fetal outcomes.